Supra‐nutritional levels of α‐tocopherol maintain the oxidative stability of n‐3 long‐chain fatty acid enriched subcutaneous fat and frozen loin, but not of dry fermented sausage. (16th March 2016) - Vossen, Els; Claeys, Erik; Raes, Katleen; van Mullem, Danny; De Smet, Stefaan
Abstract: BACKGROUND: Meat products enriched with n ‐3 fatty acids are more prone to oxidation. The aim was to investigate whether supra‐nutritional levels of α ‐tocopherol can enhance the colour and lipid oxidative stability of n ‐3 fatty acids enriched dry fermented sausages, frozen loins and subcutaneous fat. Pigs were fed a diet supplemented with 18 g kg −1 fish oil and 50, 150 or 300 mg kg −1 α ‐tocopheryl acetate. The control group received 12 g kg −1 soy oil and 150 mg kg −1 α ‐tocopheryl acetate. RESULTS: α ‐Tocopherol levels of the frozen loin, dry fermented sausage and subcutaneous fat were elevated as a result of the dietary α ‐tocopherol supplementation. Lipid oxidation occurred to the same extend in the n ‐3 fatty acid enriched frozen loins when compared to the control group. In the subcutaneous fat enriched with n ‐3 fatty acids reduced lipid oxidation was found when comparing 50 mg kg −1 versus 150 and 300 mg kg −1 . However, in the dry fermented sausages no such effect was observed and higher TBARS values were found in the n ‐3 fatty acid enriched sausages compared to the control group. Colour parameters of the loin and subcutaneous fat were not affected, whereas some significant differences in the dry fermented sausages were found. The colour stability of the frozen loins was not affected by the dietary treatments. CONCLUSION: Supra‐nutritional levels of α ‐tocopherol maintain the oxidative stability of n ‐3 fatty acid enriched frozen loins and subcutaneous fat, but not of dry fermented sausages. © 2016 Society of Chemical Industry